Methods in reproductive aquaculture : (CRC Press, 2009)
The book focuses on gamete quality and management, exploring new objectives and areas of application and research, and new tools to deal with some aspects in reproduction of aquatic species. It begins with an examination of basic methods and techniques for gamete extraction, mainly sperm collection and egg stripping in different species, then describes techniques of spawning stimulation in males and females. The volume then highlights sperm and egg quality evaluation and considers sperm analysis from a practical broodstock management point of view and in the selection of appropriate breeders. The book goes on to discuss techniques used for artificial fertilization and the procedures for obtaining modified offspring. It introduces cryopreservation procedures for sperm, oocytes, and embryos, then discusses the materials and facilities required for gamete preparation and freezing-thawing procedures. The book concludes with an extensive section detailing sperm cryopreservation protocols for fifty-six marine and freshwater species.